2020
DOI: 10.3390/polym12071544
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Controlled Release in Physically Crosslinked Poly (Vinyl Alcohol)/Iota-Carrageenan Hydrogel Blends

Abstract: This paper reports the obtaining of poly (vinyl alcohol) and ι-carrageenan blend hydrogels by physical crosslinking (consecutive freeze–thaw cycles). The two polymers were completely miscible in the weight ratio interval used in this study, as determined by solution viscometry data. Strong interactions through hydrogen bonding and forming of mixed interpolymer crystalline domains were observed, which are responsible for the formation of stable drug release-tunable matrices. The release profiles of three model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The weakly basic conjugated phenolic enone system was reported to take place at pH = 7.3 which could account for a 25% increase in the value of the tetracycline diffusion coefficients, compared to pH = 3. It has been revealed that amino groups turn out to be ionized only at pH > 8, which is well outside the pH thresholds for the human body [ 54 ]. After the TC release for 2 days, as demonstrated in Figure 11 E,F, E-CMC-CEL showed highest amount of tetracycline release at 5.06 mg g −1 dry gel, followed by E-CMC which was released at 4.37 mg g −1 dry gel.…”
Section: Resultsmentioning
confidence: 99%
“…The weakly basic conjugated phenolic enone system was reported to take place at pH = 7.3 which could account for a 25% increase in the value of the tetracycline diffusion coefficients, compared to pH = 3. It has been revealed that amino groups turn out to be ionized only at pH > 8, which is well outside the pH thresholds for the human body [ 54 ]. After the TC release for 2 days, as demonstrated in Figure 11 E,F, E-CMC-CEL showed highest amount of tetracycline release at 5.06 mg g −1 dry gel, followed by E-CMC which was released at 4.37 mg g −1 dry gel.…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan is presented as a gold candidate in pharmaceutical and biotechnological applications because of its biocompatibility, high viscosity, and gelling capacity, and the ability for its controlled release of drugs [ 9 , 34 , 116 ]. However, the fast degeneration and quick swelling of carrageenan cause the fast release of drugs with less effectivity [ 117 ]. In this regard, the interaction of different types of carrageenan with each other or other polymers is helpful to achieve ideal drug release platforms [ 118 ].…”
Section: Hybrid Carrageenan-based Platforms and Its Applicationmentioning
confidence: 99%
“…111) However, there are some controlling factors like swelling force, mechanical strength, diffusion release (matrix or reservoir system), and viscosity that need to be considered to release the drug from the matrix. 3,[112][113][114][115] Ulvan has been modified with lysozyme that has cationic charged. The complex formation results in stable nanoparticles and increasing antibacterial activity.…”
Section: Drug Deliverymentioning
confidence: 99%